Anxiety modulates the effects of emotion and attention on early vision - Ferneyhough, Emma (2012)
At attended locations emotion and attention interact to benefit contrast sensitivity, a basic visual dimension. Whether there are associated costs at unattended locations is unknown. Furthermore, emotion and attention affect response time, and anxiety modulates these effects. We investigated how trait-anxiety influences the interaction of emotion and attention on contrast sensitivity. On each trial, non-predictive precues (neutral or fearful faces) directed exogenous attention to four contrast-varying, tilted stimuli (Gabor patches). Attention was cued toward the target (valid), a distracter (invalid), or distributed over all locations. Observers discriminated target orientation, and completed self-report measures of anxiety. Effects of fearful expressions were mediated by trait-anxiety. Only high-trait anxious individuals showed decreased target contrast sensitivity after attention was diverted to a distracter by a fearful cue, and anxiety score correlated with degree of impairment across participants. This indicates that increasing anxiety exacerbates threat-related attentional costs to visual perception, hampering processing at non-threat-related locations.